Numerical simulation of thermal changes in tissues of woman's breast during menstrual cycle in different stages of its development. (8th November 2019) - Makrariya, Akshara; Pardasani, K.R.
A model is proposed to study thermal changes taking place in a woman's breast in different stages of its development due to the menstrual cycle. The changes in the physical and physiological parameters such as blood mass flow rate, metabolic heat generation and thermal conductivity due to benign changes in the breast, have been incorporated in the model. Appropriate boundary conditions have been framed based on the physical conditions of the problem. The temperature profiles have been computed and the thermal changes in the breast have been analysed during the follicular and luteal phases of the menstrual cycle in different stages of its development. The finite element method has proved to be quite flexible and powerful in the present study as it was possible to incorporate the physiology of the breast in the proposed model to generate the thermal information of the breast due to benign changes occurring in the breast such as the menstrual cycle, etc.